Direct nitrogen and phosphorus limitation of arbuscular mycorrhizal fungi a model and field test - Treseder, Kathleen K (The New phytologist, 2002)
•  Since mycorrhizal fungi constitute an important component of the soil-plant interface, their responses to changes in nutrient availability may mediate shifts in ecosystem function. We tested the hypothesis that initial soil nutrient availability may determine effects of nitrogen (N) and phosphorus (P) additions on the growth and community of arbuscular mycorrhizal (AM) fungi. •  Extraradical hyphal lengths and degree of root colonization of AM fungi were measured in control and fertilized plots along a soil fertility gradient in Hawaii. Responses of individual AM genera were assessed through immunofluorescent labeling. •  The AM biomass was increased by N and P additions in the N- and P-limited sites, respectively, and reduced by P fertilization in the fertile site only. The abundance of Scutellospora was lower under N than under P fertilization, whereas the incidence of Glomus was higher in the fertile site than the N-limited site. Gigaspora and Acaulospora did not vary among sites or treatments. •  Our results indicate that a decrease in AM abundance following nutrient additions cannot be assumed to occur and the effects may differ among AM genera and ecosystems with varying soil nutrients. Limitation of N and P may be one possible explanation